2019
DOI: 10.1002/ps.5601
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of gene‐specific dsRNA by microinjection and feeding induces RNAi response in Sri Lanka weevil, Myllocerus undecimpustulatus undatus Marshall

Abstract: BACKGROUND RNA interference (RNAi) is widely used in entomological research for functional analysis of genes and is being considered as a new tool for insect pest management. Sri Lanka weevil (SLW) is a highly polyphagous pest of agronomically important plants, but currently only a few control methods are available for this insect. RESULTS In the present study, we evaluated the stability of candidate reference genes β‐ACT, α‐TUB, EF1‐α, RPL12 and GAPDH, and identified EF1‐α as the most reliable for gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
(91 reference statements)
1
10
0
Order By: Relevance
“… Wu et al (2019) observed no effect on survival of pepper weevil ( Anthonomus eugenii ) after dietary exposure to pepper coated with dsRNA (target genes Snf7 and vATPase A ) at a concentration of 0.3 μg dsRNA/μl. Pinheiro et al (2020) observed between 43 and 93% mortality in the Sri Lanka weevil ( Myllocerus undecimpustulatus ), depending on the target gene. However, as mortality was only monitored after 26 days (dsRNA treatments were administered for 20 days), there remain critical unknowns with regard to timeliness of RNAi-induced mortality.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“… Wu et al (2019) observed no effect on survival of pepper weevil ( Anthonomus eugenii ) after dietary exposure to pepper coated with dsRNA (target genes Snf7 and vATPase A ) at a concentration of 0.3 μg dsRNA/μl. Pinheiro et al (2020) observed between 43 and 93% mortality in the Sri Lanka weevil ( Myllocerus undecimpustulatus ), depending on the target gene. However, as mortality was only monitored after 26 days (dsRNA treatments were administered for 20 days), there remain critical unknowns with regard to timeliness of RNAi-induced mortality.…”
Section: Observed Rnai Sensitivities In Coleopteramentioning
confidence: 99%
“…All these methods are useful, but there are still some shortcomings. As a new molecular biological technology, RNAi has been applied in some insects of coleoptera (Ke et al, 2018;Haller et al, 2019;Pinheiro et al, 2020). In this study, five effective primers of visual and olfactory target genes for RNAi of EAB were designed, providing a basis for RNAi-based new controlling method development of A. planipennis at adult stage.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerate primers for RPS23, 18S, 28S and RpII140 were manually designed based on conserved nucleotide sequence among other Coleoptera species. Primers for ArgK, EF1-α, RPL12, α-TUB and Prosα-2 were obtained from previous works 30,47 ( Supplementary Table S2). PCR amplifications consisted of 5 µL of 10x PCR buffer, 8 µL of MgCl 2 (50 mM), 5 µL of dNTPs mix (10 mM of each nucleotide), 8 µL of each primer (10 µM), 1.25 µL of Taq DNA Polymerase (5U/µL) (ThermoFisher Scientific), 2 µL of cDNA (diluted 10×) and 12.75 µL of nuclease-free water.…”
Section: Reference Gene Selection Gene Fragment Cloning and Primer Dmentioning
confidence: 99%